Effectiveness of Calotropis procera Leaf Extract in Treating Eimeriosis- Induced Inflammation Alteration of the Jejunum in Mice - Murshed, M; AL-Tamimi, J; Mares, M; Aljawdah, HMA; Al-Qurishy, S (Journal of the Hellenic Veterinary Medical Society, 2025)
Calotropis procera leaf extract was utilized to evaluate the anti-inflammatory and oxidative status of Eimeria papillate infection in mice. The mice were divided into five groups: Group I served as the control. In Group II, considered uninfected, a dose of 200 mg/kg of the extract was administered to evaluate toxicity. Groups III, IV, and V were infected with 1 x 103 sporulated E. papillate oocysts. Group III received no treatment. Group IV was administered 200 mg/kg extractants daily, while Group V received 25 mg/kg of toltrazuril daily via gavage. On day 5 p.i., mice were slaughtered and jejunum tissues were prepared for examination. GC-MS analysis revealed nine biologically active chemical compounds. Also, quantitative results showed phenolics, flavonoids, and tannin 160.22±0.652 GAE, 34.046±0.545 QE, and 65.869±0.263 TAE/(mg/g DW), respectively. Moreover, IC50 was obtained at 44.2±0.007 g/mL for Hep-G2 cell lines. Results showed statistically significant differences in mice that received a dose of 200 mg/kg of the extract, compared to the infected group (P ≤ 0.05), as the tissue injury within the jejunum decreased by 61%. The extract successfully reverses the effects of the E. papillate infection on glutathione, malondialdehyde, and total protein levels. It has been demonstrated that extract possesses anti-inflammatory activities, and improves oxidative status.